Spotlight on Presentations - Jennifer Gipp (Cengage Learning, Inc, 2005)
As computer education curriculum moves down from the high school to middle school level, it's especially important that students get the skills they need at an early age. Now there is a solution that provides middle school teachers with the curricular framework needed to be successful. You can choose your books based on the applications you use rather than purchasing a textbook that covers subjects that are not even covered in your class. These flexible books that you can mix and match to suit your specific classroom needs, introduce a concept, provide practice using the application, and then allow students to use the applications in a cross-curricular scenario